2018
DOI: 10.1016/j.seizure.2018.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of free serum valproate concentration: A prospective study in patients on divalproex sodium monotherapy

Abstract: An increase in the total VPA concentration results in corresponding linear and non-linear rise in the VPA free fraction and free VPA concentration, respectively. The total daily dose of VPA should be increased in smaller increments whenever a total VPA concentration of 60 μg/mL is reached. When drug monitoring is needed, we recommend measuring the free VPA concentration. If this test is unavailable, and for patients with normal albumin levels, it can be predicted from the total VPA concentration using the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…Although several studies have demonstrated that free serum concentration has a stronger association with adverse effects than does total serum concentration, total serum concentration is adopted more widely for technical and economic reasons [ 4 , 17 ]. However, free and total VPA serum concentrations are highly discordant because of the unpredictable free fraction, particularly in case of higher total VPA serum concentration (>60 mcg/mL) and hypoalbuminemia [ 4 , 8 , 9 ]. Riker et al [ 10 ] analyzed VPA use in 15 patients in an intensive care unit and reported a considerable variation in free fraction, ranging from 15% to 89%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although several studies have demonstrated that free serum concentration has a stronger association with adverse effects than does total serum concentration, total serum concentration is adopted more widely for technical and economic reasons [ 4 , 17 ]. However, free and total VPA serum concentrations are highly discordant because of the unpredictable free fraction, particularly in case of higher total VPA serum concentration (>60 mcg/mL) and hypoalbuminemia [ 4 , 8 , 9 ]. Riker et al [ 10 ] analyzed VPA use in 15 patients in an intensive care unit and reported a considerable variation in free fraction, ranging from 15% to 89%.…”
Section: Discussionmentioning
confidence: 99%
“…Free VPA is responsible for the drug's pharmacologic effects but also for its toxicity. At a normal albumin concentration and low total serum concentration (20-60 mcg/mL), the unbound fraction of VPA is approximately 10% of the total serum concentration [8]. The unbound fraction might exceed 15% when total serum concentration is higher than 100 mcg/mL [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, free fractions of unbound compound (e.g. VPA ~0.3 -0.5 mM, phenytoin ~3 -9 µM) reflect human therapeutic concentrations more appropriately, when they are set into correlation with free in vitro concentrations of the human gastruloid model, since the E6 human gastruloid medium is free of serum albumin [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…A Japanese study 42 found a total VPA concentration of 71.2 ± 32.3 µg/mL in epilepsy patients, with a free concentration of 7.05 ± 5.84 µg/mL and a plasma protein binding rate of 90.1%. Wassim et al 35 reported a VPA protein binding rate of around 83.0% in 902 Arabians (10-75 years old), while the average free drug concentration was 18.3 µg/mL. Drisaldi et al 43 investigated 174 American adults and determined a free VPA concentration range of 7-23 µg/mL; the free VPA concentration range in an intensive care unit (ICU) of Miami was 5-17 µg/mL, while plasma protein binding levels were 48% on average.…”
Section: Associations Of Vpa Free Concentration With Total Concentration and Plasma Protein Binding Ratementioning
confidence: 99%